ESSENTIAL OIL COMPOSITION OF ELETTARIOPSIS WANDOKTHONG PICHEANS. & YUPPARACH RHIZOME FROM THAILAND - Theanphong, Orawan; Phadungcharoen, Thatree P; Jenjittikul, Thaya; Mingvanish, Withawat (Interprofessional Journal of Health Sciences, 2023)
The essential oil from the fresh rhizome of Elettariopsis wandokthong Picheans. & Yupparach (Zingiberaceae) was obtained by hydrodistillation. Forty eight compounds were identified by gas chromatography-mass spectroscopy (GC-MS) technique. The three major compounds were camphene (22.51 %), fenchyl acetate (9.11 %) and 1, 8-cineole (8.12 %). This is the first report on the chemical composition of the essential oil of E. wandokthong fresh rhizome.